(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper discusses and analyzes the effect of environmental factors on ion concentrations in urban air. Statistically mathematical method was used to analyze the measurements of air ion concentration collected in a period of several months, with ion size ranging from 0.75 to 36.6 nm. As environmental factors related to air ions, the following chemical and physical parameters of the atmospheric air were analyzed: CO, NO, NO2, NOx, SO2, O3, PM10, PM2.5, temperature, relative humidity, wind speed and direction. When analyzing data in this combination, there is often a problem of multicollinearity between air chemical and physical parameters. This paper addresses this problem by using the component regression. Regression equations were elaborated to understand the dependence of concentrations of various classes of positive and negative air ions on chemical and physical parameters of the air.